A bioassay technique to assess the molluscicidal effects of microbes - Howlett, S.A.; Burch, G.; Sarathchandra, U.; Bell, N.L. (New Zealand Plant Protection, 2009)
Terrestrial slugs (Order Stylommatophora) can cause significant damage in cropping and pastoral systems Pathogenic microbes have long been shown to have potential as biocontrol agents for insect pests and a number of retail products are available but there is no equivalent product for molluscs A research program is underway to investigate the potential of micro organisms as slug biocontrol agents and this paper describes a bioassay methodology that can be used to assess the molluscicidal properties of bacterial isolates Its feasibility has been demonstrated in laboratory tests against pest slugs of the genus Deroceras Fourteen bacterial strains were screened by feeding them to the slugs in a mix based on oat bran a food that is highly palatable to these molluscs Mortality was assessed 3 and 4 days after introduction of the treated food Two of the bacterial strains tested resulted in significant mortality killing 100 slugs within 4 days